Ossicular chain reconstruction in chronic otitis media: hearing results and analysis of prognostic factors - Kotzias,Syriaco Atherino (2020)
Abstract Introduction The goal of ossiculoplasty is to improve hearing and the success of this procedure depends on several factors. Objective Analyze the hearing results in patients with chronic otitis media undergoing ossicular chain reconstruction, as well as predictive factors for successful surgery. Methods Charts of patients undergoing ossiculoplasty between 2006 and 2016 were reviewed. Sixty-eight patients were included, totaling 72 ears. The following data was analyzed: gender, age, smoking status, laterality, pathology, audiometric exams, type of surgery, previous surgery, characteristics of the middle ear, otorrhea and ossicular chain status. Patients were also classified according to two indices: middle ear risk index and ossiculoplasty outcome parameter staging. The results were evaluated by comparing the air-bone gap before and after surgery. The success of reconstruction was defined as air-bone gap ≤20 dB and the improvement of speech reception Thresholds, calculated through the mean frequencies 0.5, 1, 2 and 3 kHz. Results Reconstruction success rate was 61%. The mean preoperative air bone gap was 34.63 dB and decreased to 17.26 dB after surgery. There was a correlation between low risk in middle ear risk index and ossiculoplasty outcome parameter staging indices with postoperative success. The most frequently eroded ossicle was the incus and the type of prosthesis most used was tragal cartilage. In the patients without incus, we achieved success in 74.2% of the surgeries. In the absence of the stapes, the success rate decreased to 63.3%. In the absence of the malleus, 85% of the patients had and air bone gap ≤20 dB. Conclusion We achieved good audiometric outcomes in ossiculoplasty and the results are comparable to other centers. Ossicle status influenced postoperative results, especially in the presence of stapes. We also concluded that the indexes analyzed may help to predict the success of the surgery.